WORKSHOP PENYUSUNAN PROPOSAL PENELITIAN TINDAKAN KELAS (PTK) DI SMA NEGERI 2 KUALA MANDOR B - Nuraini Asriati; Herkulana Herkulana; Jumardi Budiman; Sandra Fitria; Sri Ernawati; Sidiq Kurniawan (STKIP Persada Khatulistiwa Sintang, 2022)
ABSTRACTBased on the initial observations and interviews conducted with teachers at SMA Negeri 2 Kuala Mandor B, the obstacles encountered by teachers in implementing and writing Classrom Action Research (CAR) at school include; teachers' assumption that implementing and writing CAR is difficult to implement due to lack of understanding of CAR; lack of mentoring process by colleagues/school principals/education offices for teachers who carry out CAR; the lack of training activities for implementing and writing CAR which is directly technical in nature so that teachers are reluctant to attend seminars that are theoretical in nature; and the lack of facilities for teachers to publish the results of their CAR reports, thereby reducing interest and motivation to carry out CAR. The importance of this workshop being carried out in order to provide applicable understanding to teachers as an important subject in efforts to improve the quality of continuing education through classroom action research activities. The method of implementing PKM is by delivering material online and offline as well as guiding the preparation of CAR proposals online. The results of the PKM implementation are that all participants have a title plan and research outline which will then be developed into a proposal/action plan.Keywords: training, proposal, CARABSTRAKBerdasarkan observasi dan wawancara awal yang dilaksanakan pada guru di SMA Negeri 2 Kuala Mandor B, kendala yang ditemui guru dalam melaksanakan dan menulis PTK di sekolah antara lain; anggapan guru bahwa melaksanakan dan menulis PTK adalah hal yang sulit dilaksanakan akibat kurangnya pemahaman tentang PTK; kurangnya proses pendampingan oleh rekan sejawat/ kepala sekolah/ pihak dinas pendidikan terhadap guru yang melaksanakan PTK; minimnya kegiatan pelatihan pelaksanakan dan penulisan PTK yang langsung bersifat teknis sehingga guru enggan mengikuti seminar yang sifatnya teoritis; dan minimnya sarana bagi guru untuk mempublikasikan hasil laporan PTK yang dilakukan sehingga menurunkan minat dan motivasi untuk melaksanakan PTK. Pentingnya workshop ini dilaksanakan agar memberikan pemahaman aplikatif kepada guru selaku subjek penting dalam upaya perbaikan kualitas pendidikan berkelanjutan melalui kegiatan penelitian tindakan kelas. Metode pelaksanaan PKM yakni dengan penyampaian materi secara daring dan luring serta pembimbingan penyusunan proposal PTK secara daring. Hasil pelaksanaan PKM yakni seluruh peserta telah memiliki rencana judul dan outline penelitian yang selanjutnya akan dikembangkan menjadi proposal / rencana Tindakan.Kata Kunci: pelatihan, proposal, PTK